The Body as a Source of Meaning in the Culture of Remembrance: The Reputational Entrepreneurship of the Characters of Yugoslav National Heroes - Ivana Lučić Todosić (University of Belgrade, 2020)
The aim of this paper is to explore the patterns and meanings to be found in the characters of Yugoslav national heroes who met a violent death in World War II. These are heroes who belong to the type of martyr heroes, and their sacrifice is highly rated in all patriotic mythologies. Created to denote the heroism of the chosen, they have sublimated the meaning and symbolism of one remembrance of the war. The death of these national heroes will be analyzed through their official biographies, which served to represent the characters of the National Heroes of Yugoslavia and keep the heroic symbol-names ever present in the collective group memory. Through their characters, a specific wartime experience and the martyr’s death of the national hero who died for the freedom of the Yugoslav peoples, as seen by the victors in this war drama, were transmitted to the citizens of Yugoslavia. Various patterns of wartime heroism (warrior, martyr, leader heroism) were represented as national patriotism, and the fighters and martyrs of the war of national liberation were named. The characteristics of  the reputational entrepreneurship of these heroes’ characters are specifically explored, taking into account the characteristics of the discourse through which they were interpreted and presented. On the other hand, the limitations of this discourse provide an opportunity to deconstruct certain common traits of a certain hero type and discover the latent meanings conveyed by the characters of Yugoslav national heroes as actors of a historical-political myth.